Teaching and Learning Alternatives to a Comparative Advantage Motivation for Trade. (October 2016) - Self, James K.; Becker, William E.
Introductory economics courses emphasize opportunity cost, comparative advantage, and specialization to show the benefits of trade. We assert that this emphasis leads to erroneous student mind-set that trade requires specialization based on comparative advantage. We test students who have been exposed to the typical textbook and classroom presentation of specialization and trade with real but paradoxical situations where the same goods are both imported and exported by a country. Students are found to generally understand comparative advantage calculations but wrongfully apply the idea to this multiproduct trade situation for which specialization is not relevant.